Post-colonoscopy colorectal cancer rates in the Swedish IBD and non-IBD population: Something missed or something faster? - Yılmaz Ürün, Yonca; Üstündağ, Yücel (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Yılmaz Ürün Y, Üstündağ Y. Post-colonoscopy colorectal cancer rates in the Swedish IBD and non-IBD population: Something missed or something faster? Turk J Gastroenterol 2019; 30(9): 860-2.